Invasive meningococcal disease epidemiology and characterization of Neisseria meningitidis serogroups, sequence types, and clones; implication for use of meningococcal vaccines - Chen Stein-Zamir; Hanna Shoob; Nitza Abramson; Colin Block; Natan Keller; Joseph Jaffe; Lea Valinsky (Taylor & Francis Group, 2019)
Background and aims: Neisseria meningitidis (N. meningitidis) is a Gram-negative bacterium that can cause life-threatening invasive infections referred to as invasive meningococcal disease (IMD). In the last decade the incidence of IMD in Israel is about 1/100,000 population annually. We aimed to describe the epidemiology of IMD in Israel combining epidemiological data and characterization of N. meningitidis isolates. Methods: Invasive infection caused by N. meningitidis is a notifiable disease in Israel. Data were collected by epidemiological investigations and control measures were employed. Laboratory work-up included serogrouping, N. meningitides molecular characterization and whole-genome sequencing. Results: During 1998-2017, 1349 cases of IMD were notified in Israel (mean annual incidence rate 0.94/100,000). The peak incidence rates were observed in infants under 1 year of age (10.9/100,000). Case fatality rate was 9.7%. The majority of the N. meningitidis isolates were of serogroup B (67.9%). During 2007-2017, three clonal complexes (CC) 32, 41/44 and 23 (hyper-invasive clonal complexes) were the leading CC (61%). CC32 was the leading CC causing meningococcemia and mortality. In 2017, 35 isolates were tested for 4CMenB antigens variants; of the serogroup B isolates tested 46.7% showed a match to one or more antigens (fHbp or PorA:VR1), most were ST32 (CC32). Conclusions: Preliminary analysis based on limited number of samples suggests that the 4CMenB coverage would be about half the strains; further research is necessary. Integration of clinical, epidemiological and laboratory data is essential to support decision-making on the introduction of the novel MENB vaccines in Israel.